SOLID WASTE POLLUTION IN THE SEBANGAU RIVER, KERENG BANGKIRAI, PALANGKA RAYA CITY, CENTRAL KALIMANTAN - Maria T.L Manik; Danar A.W. G, ST.,M (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2025)
The Sebangau Kereng Bangkirai River is still a destination in the city of Palangkaraya, Central Kalimantan. The natural scenery on the left and right of the river path is still original. The eyes of visitors or tourists are spoiled by the beauty of the black water of the peat swamp, the construction of the Kereng Bangkirai pier entrance gate building is unique and has a strong ethnic nuance. Starting from the motifs, colors and shapes highlight the characteristics of the Dayak. However, problems arise for the people who live on the banks of the river. Some residents do not maintain and preserve their environment on the banks of the Sebangau Kereng Bangkirai River. The existence of people throwing solid waste directly into the river has resulted in outbreaks of disease and environmental pollution in the Sebangau River area, there is waste dumped by local residents in the form of their daily activities, namely used laundry and food or drinks. This study aims to determine the cause of pollution in the Kereng Bangkirai River in the Kereng Bangkirai River environment. This study was carried out directly in the field by interviewing the community and monitoring community activities. Solid waste can damage the surrounding environment by causing unpleasant odors due to the waste being thrown away by people directly into the river under people's homes and the waste piling up and being scattered.